Bowel function in patients with urinary diversion: a gender-matched comparison of continent urinary diversion with the ileocecal pouch and ileal conduit - Frees, Sebastian; Thüroff, Joachim W.; Stein, Raimund (World journal of urology, 2017)
PurposeTo evaluate stool habits and associated quality of life (QoL) in a matched pair analysis of patients who underwent continent cutaneous diversion using the ileocecal segment [Mainz pouch I (MzPI)] with an intussuscepted ileal nipple as efferent segment with those receiving an ileal conduit (IC) after radical cystectomy.MethodsWe identified 250 patients who underwent radical cystectomy and urinary diversion (UD) with either MzPI with an ileal nipple or IC in our database. A detailed history of stool habits using the modified Wexner score was obtained, and questions addressing general lifestyle, comparison of symptom differences before and after surgery considering bowel function as well as bowel-associated QoL were assessed.ResultsForty-five age- and sex-matched pairs could be compared. Overall, stool incontinence (p = 0.481) and the Wexner score (p = 0.464) revealed no differences between both groups. However, patients with MzPI as compared to those with IC had significant higher rates of stool frequency (53 vs 31 %), softer stool consistencies (60 vs 13 %), diarrhea (62 vs 20 %) and a lower rate of constipation (4 vs 22 %). Patients with MzPI had a trend toward lower bowel-associated QoL compared with patients with IC. Similarly, the MzPI group reported a significantly impaired overall postoperative QoL (51 %) compared to the IC group (29 %) (p = 0.024).ConclusionsPatients following UD by MzPI have an increased stool frequency and softer stool consistency. However, there is no difference between both groups in terms of de novo stool incontinence. Change in bowel habits should be part of preoperative informed consent in any kind of UD. Careful patient selection is of paramount importance.
First online 12 October 2016
Gesehen am 30.04.2018